EVALUATION OF 2016-2021 STRATEGIC PLANNING PROCESS OF SEMARANG CITY DEPARTMENT OF TRANSPORTATION, COMMUNICATION, AND INFORMATION - Pamalis, Rezza; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
This research was conducted to evaluate the strategic planning process held by Semarang city Department of Transportation, Communication, and Information and to identify the supporting factors and the obstacles of the strategic planning process. This research was conducted because the strategies and the policies of â€œTelecommunications Infrastructure Improvement Throughout The Regionâ€ are only written in the 2005-2025 RPJPD of Semarang City but not in the 2016-2021 RPJMD of Semarang City and 2016-2021 Strategic Planning of Semarang City Department of Transportation, Communication, and Information but only written in 2017 Work Planning Program of Semarang City Department of Transportation, Communication, and Information. This research is a qualitative descriptive study with data collection through interviews and document studies. The informants that were interviewed by the researcher is the strategic plan maker team of Semarang city Department of Transportation, Communications, and Information. In this study, the researcher evaluated using the stages of the strategic planning process. The result of this research is that the evaluation of the strategic planning process is still not optimal. The result is known through research that shows that the stages to identify the mandate of organizations lacked the needed depth aside from Semarang city RPJMD, which is Semarang city RPJPD. Moreover, in the stage of creating an effective organization vision, Semarang city Department of Transportation, Communication, and Information did not envisioned its own vision for the better future and instead opted to follow the vision of the head of the region without even looking at the strategic issue that is chosen by the organization based on the acts in effect. The advice given by the researcher is to conduct a closer look into all of Semarang city document of plans, perform a closer look into all of the acts and regulations on regional development planning with regard to Semarang city, conduct regular consultations with the Regional Development Planning Agency of Semarang city, and adding human resources to alleviate the overload of work for each employee with the applicable regulations. The writer advised another strategic planning researchers to take a deeper look on all the steps of strategic planning, especially the step that concerns the initiation of strategic planning and the steps that concerns the mandate of the organization because it involves third-party subjects and is under the authority of an organization.